Does Lidocaine Shorten Seizure Duration in Electroconvulsive Therapy? - López-Ilundain, Jose; Prados, Alejandro Ballesteros; Enriquez, Ángela S. Rosero; Enguita-Germán, Mónica; Rosquil, Estefania Uriarte; Gil, Jose López; Fábrega, Ana Marmol; Martinez de Zabarte Moraza, Estitxu; Maughan, Alex R.; Yoldi-Murillo, Javier (Pharmacopsychiatry, 2023)
Background Electroconvulsive therapy (ECT) is an effective short-term treatment for schizophrenia and depression, amongst other disorders. Lidocaine is typically added to reduce pain from intravenous propofol injection. However, depending on the dose used in the ECT setting, it can shorten seizure duration. The aim of this study was to investigate the effect of lidocaine dose on seizure duration.Methods This retrospective, naturalistic cohort study included 169 patients treated with ECT. We examined 4714 ECT sessions with propofol or propofol plus lidocaine. Ictal quality was manually rated by visual inspection. The main outcome of this study was the relation of lidocaine with seizure duration after controlling for socio-demographic, ECT, and other anesthetic variables.Results There was a significant negative association between lidocaine usage and seizure duration. Multivariate analyses showed that seizure duration was shortened by an average of 3.21 s in sessions with lidocaine. Moreover, in this subgroup, there was a significant negative dose-dependent association between lidocaine dose and seizure length. Complementarily, a significant positive association between preictal BIS and seizure length was found in the subgroup of sessions where preictal was used.Conclusions We provide additional evidence highlighting the importance of caution regarding lidocaine dosing due to the effect on seizure length in the ECT setting. It is advisable for clinicians to exercise caution when administering lidocaine regarding its dosing and seizure length in ECT settings. Future investigation is needed to assess causal relationships by studying certain vulnerable groups or employing other charge calculation techniques, such as the titration method.
Keywords: electroconvulsive therapy; lidocaine; seizure length; bispectral index; propofol